Bombyx mori Silk Fibroin Regeneration in Solution of Lanthanide Ions: A Systematic Investigation - Rizzo, Giorgio; Lo Presti, Marco; Giannini, Cinzia; Sibillano, Teresa; Milella, Antonella; Guidetti, Giulia; Musio, Roberta; Omenetto, Fiorenzo G.; Farinola, Gianluca M. (Frontiers in Bioengineering and Biotechnology, 2021)
Silk Fibroin (SF) obtained from Bombyx mori is a very attractive biopolymer that can be useful for many technological applications, from optoelectronics and photonics to biomedicine. It can be processed from aqueous solutions to obtain many scaffolds. SF dissolution is possible only with the mediation of chaotropic salts that disrupt the secondary structure of the protein. As a consequence, recovered materials have disordered structures. In a previous paper, it was shown that, by modifying the standard Ajisawa’s method by using a lanthanide salt, CeCl3, as the chaotropic agent, it is possible to regenerate SF as a fibrous material with a very ordered structure, similar to that of the pristine fiber, and doped with Ce+3 ions. Since SF exhibits a moderate fluorescence which can be enhanced by the incorporation of organic molecules, ions and nanoparticles, the possibility of doping it with lanthanide ions could be an appealing approach for the development of new photonic systems. Here, a systematic investigation of the behavior of degummed SF in the presence of all lanthanide ions, Ln+3, is reported. It has been found that all lanthanide chlorides are chaotropic salts for solubilizing SF. Ln+3 ions at the beginning and the end of the series (La+3, Pr+3, Er+3, Tm+3, Yb+3, Lu+3) favor the reprecipitation of fibrous SF as already found for Ce+3. In most cases, the obtained fiber preserves the morphological and structural features of the pristine SF. With the exception of SF treated with La+3, Tm+3, and Lu+3, for all the fibers re-precipitated a concentration of Ln+3 between 0.2 and 0.4% at was measured, comparable to that measured for Ce+3-doped SF.